Sociocultural factors influencing breastfeeding practice and maternal feeding in a semi-urban community in Mexico - Romero Morales, Perla Patricia (2023)
Objective: To analyze the sociocultural factors that influence the practice of breastfeeding and maternal nutrition. Method: It is a qualitative exploratory study, with non-probabilistic sampling using the snowball technique, in women aged 18 to 50 years, conducting a semi-structured interview with prior signature of informed consent. Results: Twenty-one women in the last trimester of pregnancy or breastfeeding were interviewed, 12 first-time mothers and 9 non-first-time mothers; most of them with an age range of 20 to 29 years. The sociocultural categories identified about breastfeeding beliefs and breastfeeding practice were emotion, knowledge, attachment, difficulty, inequality; they referred that breastfeeding is a unique experience that creates a mother-child bond, which provides security and protection to their children. In addition, myths/beliefs about maternal feeding were identified, such as the use of beverages that favor milk production. Conclusion: The environment in which mothers find themselves is determinant for the initiation, duration and success of breastfeeding, hence the importance of knowing the mothers' point of view. Breastfeeding can be influenced by cultural discourses or practices that sometimes turn out to be contradictory, some of them lacking scientific foundations, so it is important to continue carrying out this type of studies, where it is possible to determine in depth what are the difficulties or obstacles that arise in order to carry out a good promotion and encouragement of breastfeeding.